First 3D-printed complex inorganic polycrystalline scintillator. Issue 30 (22nd May 2017) - Dosovitskiy, G. A.; Karpyuk, P. V.; Evdokimov, P. V.; Kuznetsova, D. E.; Mechinsky, V. A.; Borisevich, A. E.; Fedorov, A. A.; Putlayev, V. I.; Dosovitskiy, A. E.; Korjik, M. V.
Abstract : Polycrystalline scintillator YAG:Ce was 3D-printed using stereophotolithography and sintered; it has shown light yield 60% higher than YAG:Ce single crystal. Abstract : YAG:Ce scintillating material was obtained using 3D printing for the first time. A green body was printed using a stereophotolithography approach from co-precipitated powders and then sintered at 1600 °C in air to afford translucent ceramics. The scintillation light yield using 5.5 MeV α-particle excitation was more than 60% higher than that of the reference YAG:Ce single crystal.